Impact of eight widely consumed antibiotics on the growth and physiological profile of natural soil microbial communities. (October 2022) - Pino-Otín, María Rosa; Ferrando, Natalia; Ballestero, Diego; Langa, Elisa; Roig, Francisco J.; Terrado, Eva M.
Abstract: Antibiotics' (ATBs) occurrence in soil ecosystems has a relevant effect in the structure and functionality of edaphic microbial communities, mainly because of their amendment with manure and biosolids that alter their key ecological functions. In this study, the impact of eight widely consumed ATBs on a natural soil microbial community, characterized through 16 S rRNA gene sequencing, was evaluated. Changes induced by the ATBs in the growth of the soil microbiota and in the community-level physiological profiling (CLPP), using Biolog EcoPlates™, were measured as endpoint. The eight assayed ATBs lead to a significant decrease in the growth of soil microbial communities in a dose-dependent way, ordered by its effect as follows: chloramphenicol > gentamycin > erythromycin > ampicillin > penicillin > amoxicillin > tetracycline > streptomycin. Chloramphenicol, gentamycin, and erythromycin adversely affected the physiological profile of the soil community, especially its ability to metabolize amino acids, carboxylic and ketonic acids and polymers. The analysis of the relationship between the physico-chemical properties of ATBs, as well as their mechanism of action, revealed that, except for the aminoglycosides, each ATB is influenced by a different physico-chemical parameters, even for ATBs of the same family. Significant effects were detected from 100 μg mL to 1, concentrations that can be found in digested sludge, biosolids and even in fertilized soils after repeated application of manure, so cumulative and long-term effects of these antibiotics on soil environment cannot be ruled out. Graphical abstract: Image 1 Highlights: Ecotoxicity of 8 antibiotics on 16 S rRNA sequenced microbial soil community. Chloramphenicol, Gentamycin and Erythromycin were the most harmful antibiotics. All assessed antibiotics provoked a decrease on soil microbial growth from 100 μg/mL. All assessed antibiotics altered soil Community-Level Physiological Profiling. Amino-Carboxylic-Ketonic acids and Polymers were the most affected metabolisms.